Copper-catalysed conjugate addition to sulfinimines - Gaunt, Anthony John (2016)
The synthesis of a series of [alpha],[beta]-unsaturated sulfinimines is described. Their reaction in the presence of copper-based nucleophiles to yield 1,4-addition products is analysed in terms of yield and d.r. values and reported herein. After an introductory chapter, the first section of this thesis describes the synthesis and reaction of (R)-(E)-N-((E)-but-2’-en-1’-ylidene)-2-methylpropane-2-sulfinamide in the presence of a series of copper-based nucleophiles – most notably Gilman nucleophiles – displaying yields of up to 54% and 3:2 d.r. values. The second section of this thesis describes the synthesis of a range of cinnamaldehyde-derived sulfinimines and their reaction in the presence of copper-based nucleophiles – this time derived from alkyl aluminium reagents. Up to quantitative yields and d.r. values of 1:>20 are reported. In addition, methodology for the synthesis of cinnamaldehyde precursor derivatives via a Meyer-Schuster rearrangement is discussed along with the qualitative identification of competing reactions.